Information in tournaments under limited liability - Jörg Budde (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
The problem of designing tournament contracts under limited liability and alternative performance measures is considered. Under risk neutrality, only the best performing agent receives an extra premium if the liability constraint becomes binding. Under risk aversion, more than one prize is awarded. In both situations, performance measures can be ranked if their likelihood ratio distribution functions differ by a mean preserving spread. The latter result is applied to questions of contest design and more general forms of relative performance payment.
Keywords: D82; M52; M54; 330; contest; information; likelihood ratio distribution; tournament